Anchorage control in the differential straight-arch technique and the tip-edge bracket - Salud, Margarita A.
The purpose of this paper is twofold: first, to investigate anchorage control in four premolar extraction cases using the concept of Differential Straight-Arch Technique and the Tip-Edge bracket, and second, to compare anchorage loss in the maxillary arch between first premolar extraction and second premolar extraction cases in class II division 1 malocclusions. Data were obtained from the pretreatment and post treatment lateral cephalometric radiographs of 30 patients, 13 boys and 17 girls, who were treated exclusively with the Differential Straight-Arch Technique and the Tip-Edge brackets. Of the 30 patients selected, 20 had four first premolar extractions and 10 had maxillary second and mandibular first premolar extractions. For the purpose of comparing the anchorage values between first and second premolar extractions cases, the sample was divided into two groups. Subjects with four first molar extractions were placed in the first premolar group. Subjects with maxillary second and mandibular first premolar extractions were placed in the second premolar group. Comparison was calculated only in the maxillary arch. T-text was used to compare the measurements obtained in this study as against those gathered from another study comparing anchorage management between the Edgewise and Begg techniques. The major finding of this study is the clinical effectiveness of Differential Straight-Arch Technique and the Tip-Edge brackets as a means of controlling intraoral anchorage in Class II division 1 malocclusion. The first premolar group showed better anchorage control compared to the second premolar group.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Orthodontic anchorage procedures; Orthodontics